Correction of severe columella and tip retraction in silicone implanted Asian short noses - Sertel, Serkan; Venara-Vulpe, Ioana-Irina; Pasche, Philippe (Journal of otolaryngology, head & neck surgery, 2016)
Silicone Implants and other alloplastic materials are frequently used in rhinoplasty to augment Asian short noses. However, nasal deformities as a result of implant-related infections are increasing in incidence. The resulting tissue scarrings hinder the application of traditional techniques of lengthening short noses. The following paper presents a technique to correct severe postoperative retractions of the tip and columella caused by silicone implants.
Gesehen am 05.05.2020